Russia's Goals and Priorities in the Russia-Ukraine Conflict - Kamil, Fadly Muhammad; Sudirman, Arfin (Journal of Public Representative and Society Provision, 2025)
Based on Colin Gray’s defense planning theory, Russia’s territorial control in Ukraine reflects a clear strategic defense objective to strengthen its position in Eastern Europe. The success of Russia’s defense strategy is influenced by the interplay between political policies, military power, and the ability to adapt to close-range conflict situations. This territorial control is not merely a result of military conflict but also an integral part of a long-term plan to achieve broader political goals. Additionally, the motivation of Russian human resources in Ukraine demonstrates a well-planned and directed strategic approach. The high number of volunteers and the motivation of troops indicate Russia’s efforts to achieve its objectives through optimizing human resource partnerships. The prioritization of Ukraine’s natural resources also reflects Russia’s strategy to enhance its geopolitical position and fulfill its economic needs. This resource control not only provides financial advantages but also strengthens Russia’s military capabilities. Therefore, the interplay between political policies, military power, and the ability to adapt to dynamic situations is a key factor in Russia’s defense strategy during this conflict.